Novel insight into FCSK‐congenital disorder of glycosylation through a CRISPR‐generated cell model - Fazelzadeh Haghighi, Maryam; Jafari Khamirani, Hossein; Fallahi, Jafar; Monfared, Ali Arabi; Ashrafi Dehkordi, Korosh; Tabei, Seyed Mohammad Bagher (Molecular genetics & genomic medicine, 2024)
Background FCSK‐congenital disorder of glycosylation (FCSK‐CDG) is a recently discovered rare autosomal recessive genetic disorder with defective fucosylation due to mutations in the fucokinase encoding gene, FCSK. Despite the essential role of fucokinase in the fucose salvage pathway and severe multisystem manifestations of FCSK‐CDG patients, it is not elucidated which cells or which types of fucosylation are affected by its deficiency. Methods In this study, CRISPR/Cas9 was employed to construct an FCSK‐CDG cell model and explore the molecular mechanisms of the disease by lectin flow cytometry and real‐time PCR analyses. Results Comparison of cellular fucosylation by lectin flow cytometry in the created CRISPR/Cas9 FCSK knockout and the same unedited cell lines showed no significant change in the amount of cell surface fucosylated glycans, which is consistent with the only documented previous study on different cell types. It suggests a probable effect of this disease on secretory glycoproteins. Investigating O‐fucosylation by analysis of the NOTCH3 gene expression as a potential target revealed a significant decrease in the FCSK knockout cells compared with the same unedited ones, proving the effect of fucokinase deficiency on EGF‐like repeats O‐fucosylation. Conclusion This study expands insight into the FCSK‐CDG molecular mechanism; to the best of our knowledge, it is the first research conducted to reveal a gene whose expression level alters due to this disease. The current study exploring FCSK‐CDG through a CRISPR‐generated cell model demonstrated the effect of this disease on EGF‐like repeats O‐fucosylation by revealing NOTCH3 as the first identified gene whose expression level alters due to FCSK‐CDG. In addition, it suggested a probable effect of this disease on secretory glycoproteins.